SECONDARY PRE-SERVICE SCIENCE TEACHERS' TEACHING COMPETENCE: THEORY TO PRACTICE - Ramirez, Iris April (International Online Journal of Education and Teaching, 2021)
The study assessed the teaching competence of the secondary pre-service science teachers in terms of teaching knowledge, teaching skills, and attitude. The study made use of quantitative research approach (descriptive comparative research design). The validated instruments (Scale) was distributed to the respondents (n=45; Secondary Pre-service Science Student Intern) and a purposive sampling was utilized on selected Tertiary Education Institutions. Weighted means and Two-tailed T- test of dependent means at the level of significance α = 0.05 were applied. The assessment of the teaching competence has shown that the pre-service teachers were competent. Results revealed that the level of knowledge was very good, level of teaching skills was high and attitude was very positive. Results also revealed that there was no significant difference before and after practice teaching in terms of knowledge and attitude. Yet, for teaching skills, there is a significant difference before and after practice teaching.